The Existence of Diploma Retention by Companies as a Guarantee in Employment Relations and Legal Protection for Workers in Indonesia - Dinda Bhawika Wimala Pastika (Electronic Journal of Education, Social Economics and Technology, 2025)
In today's world, it is still a widespread practice for employers to retain diplomas as a reassurance in job relationships across different industries. This occurs due to the absence of clear legal grounds within Indonesia’s labor law system. Fundamentally, this practice raises legal issues as it pertains to the right of ownership over personal documents and the potential violation of principles of worker protection as stipulated in Law No. 13 of 2003 on Manpower, Law No. 39 of 1999 on Human Rights, and the principle of contractual fairness. This research intends to investigate the occurrence of diploma retention practices in job relationships and to explore the types of legal safeguards that can be offered to employees. Using a normative-juridical approach and case study method, this article finds that withholding diplomas contradicts the principles of freedom to work and legal certainty, and potentially constitutes a form of indirect coercion that may be subject to civil and/or criminal litigation. The need for explicit regulation and stricter labor supervision is the primary recommendation to prevent similar practices in the future.